KESEHATAN KEUANGAN PT. PUPUK KALTIM - LCA. Robin Jonathan, Gorbi Alex Adi Suroso (EKONOMIA, 2015)
Gorbi Alex. 2013, Evaluation of the Financial Health of PT. PUPUK KALTIM, under the guidance of Mr. LCA. Robin Jonathan and Mr. Adi Suroso.The problem in this study is whether the financial health of PT. PUPUK KALTIM meets the healthy classification based on the SK Menteri BUMN No. Kep-100 / MBU / 2002.From the analysis of the financial statements. PT. PUPUK KALTIM  known ROI experienced a sharp decline in 2011 amounted to 77.57, increased by 11.53% in 2011 and dropped by 56% in 2012, the current ratio increased from the year 2010 up to 2012 showed a good development , Each of the years in question has a value of 5 because it is in the range 125 <= X, collection periods progressed in 2011, where the days of collection of receivables could be reduced as much as 23.14% in 2010 but increased by 38.48% on year 2012, inventory turnover continued to decline from the year 2011 turnover fell as much as 15.24% and in 2012 fell as much as 1.36%, total asset turnover decreased in 2011 by 0.02% and rose by 6.96% on year 2012, total equity to total assets increased from 2010 to 2012 and survived at range50 <= <60 with a value of 8.5.               Known financial health of PT. PUPUK KALTIM from 2010 up to 2012 each have a healthy category "A" with an average score of 68.5 for each of the years in question and the total score of 205.5 in order to know the company has a healthy category "AAA" in three years analyzed.